2012
DOI: 10.1111/j.2042-7158.2012.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin-mediated expression of Nrf2 and upregulation of antioxidant status in senescent rat heart

Abstract: Hesperidin could be useful in protecting cardiomyocytes against age-related increase in oxidative stress mediated by Nrf2 upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 58 publications
(87 reference statements)
5
55
0
Order By: Relevance
“…This result suggests that flavanones of the Citrus genus could have an important impact on the improvement of endogenous anti-oxidant defences in dyslipidaemia. Very recently, hesperidin has been demonstrated to elevate anti-oxidant defences through increasing Nrf2 expression, suggesting an anti-ageing effect of this flavonoid on senescent rat hearts [34]. Similar results emerged from an in vitro study on H9c2 cells in which naringenin significantly reduced the production of beta-galactosidase, a typical marker of senescence, after doxorubicin treatment [49].…”
Section: Putative Mechanisms Of Action Responsible For the Cardiovmentioning
confidence: 67%
“…This result suggests that flavanones of the Citrus genus could have an important impact on the improvement of endogenous anti-oxidant defences in dyslipidaemia. Very recently, hesperidin has been demonstrated to elevate anti-oxidant defences through increasing Nrf2 expression, suggesting an anti-ageing effect of this flavonoid on senescent rat hearts [34]. Similar results emerged from an in vitro study on H9c2 cells in which naringenin significantly reduced the production of beta-galactosidase, a typical marker of senescence, after doxorubicin treatment [49].…”
Section: Putative Mechanisms Of Action Responsible For the Cardiovmentioning
confidence: 67%
“…Some authors have found an increase of catalase expression and/or activity in cells in the presence of flavonoids [17][18][19][20][21]. This effect probably results from flavonoidinduced activation of redox-sensitive Nrf2 signaling pathway, which regulates expression of phase II detoxifying and antioxidant enzymes [21]. Others have observed no effect or even a decrease of catalase expression and activity in cells after flavonoid treatment/digestion [22,23].…”
Section: Introductionmentioning
confidence: 95%
“…The influence of flavonoids on catalase activity has been reported in some papers, the results are, however, contradictory. Some authors have found an increase of catalase expression and/or activity in cells in the presence of flavonoids [17][18][19][20][21]. This effect probably results from flavonoidinduced activation of redox-sensitive Nrf2 signaling pathway, which regulates expression of phase II detoxifying and antioxidant enzymes [21].…”
Section: Introductionmentioning
confidence: 98%
“…This hypothesis has been verified by culturing mouse lenses with and without sulforaphane and then measuring the activity of TrxR, a very prominent member of the NADPH-disulfide oxido-reductase class of enzymes, including glutathione reductase. However, we first selected TrxR for this study in view of its activity with a wider spectrum of substrates, such as ubiquinone, lipoic acid and its amide, lipid hydro peroxide, vitamin K3, p53, hydrogen peroxide, dehydroascorbate, ascorbyl radicals, and peroxides, in addition to the protein disulfides 4349. On the other hand, glutathione reductase is active only with glutathione disulfide (GSSG), without any effect on dehydroascorbate, peroxides, and other substrates referred to above.…”
Section: Discussionmentioning
confidence: 99%